Pengaruh Karakteristik Usaha Wajib Pajak Badan Terhadap Tingkat Kepatuhan Berdasarkan Pengukuran Reporting Compliance (Studi Pada Kantor Pelayanan Pajak Pratama Surabaya Sawahan) - Umy Anisari Khulsum; Made Dudy Satyawan (Jurusan Akuntansi Fakultas Ekonomi Universitas Negeri Surabaya, 2014)
AbstractTax is important source of state revenue for national development. One factor affecting tax revenue increase is tax payer compliance. Self assessment system that applied in Indonesia enable tax payer makes reporting non-compliance. Based on previous research conducted before tax reform 2007, many factors influence taxpayer compliance, one of them is characteristic of business. This study aims to determine the influence of business characteristics corporate tax payer toward level of compliance based on reporting compliance measurement after tax reform 2007. Characteristics of business corporate tax payers in this study include market orientation and business structure. This research method is quantitative. This study was conducted on the tax payer that registered in KPP Pratama Surabaya Sawahan. The analysis technique used is multiple linear regression. The results showed that variable market orientation affect level of compliance based on reporting compliance measurement. But, variables business structure does not affect level of compliance based on reporting compliance measurements.